Addressing Issues for Graduate Students who are Single Parents with Dependent Children: What is the Role of Adult Education? - Stacy Kimbrough; Joshua C. Collins (Adult Education Research Conference, 2015)
The purpose of this roundtable is to begin unveiling the experience of the graduate student who is also a single parent, while also suggesting supportive programs to improve their recruitment and success. This adult student population is underserved. Understanding their challenges is necessary to improve resources and student success.
Keywords: single parents; graduate students; adult education